CHITOSAN BEADS IMMOBILIZED SCHIZOPHYLLUM COMMUNE IBL-06 LIGNIN PEROXIDASE WITH NOVEL THERMO STABILITY, CATALYTIC AND DYE REMOVAL PROPERTIES - P. Sofia; M. Asgher; M. Shahid; M. A. Randhawa (Journal of Animal and Plant Sciences, 2016)
The lignin mineralizing enzymes system of white rot fungi has tremendous catalytic prospect for oxidative bioremediation of a number of toxic pollutants and many other industrial uses. Immobilization enables the reuse of enzymes and making them industrially relevant and economical biocatalysts. Schizophyllum commune IBL-06 was cultivated for the secretion of lignin peroxidase (LiP) in pre-optimized solid state fermentation medium of corn stover. A high yield of lignin peroxidase (1347.3 U/mL) was recorded in crude culture supernatant. LiP was purified (5.65 folds) by a pre-standardized four step protocol comprising ammonium sulphate fractionation, dialysis, DEAE cellulose ion exchange and Sephadex G-100 column chromatography. The 38 kDa single polypeptide S. commune IBL-06 LiP migrating as a single clear band on both native and SDS-PAGE gels. The purified enzyme was then immobilized on chitosan beads activated with gluteraldehyde (cross-linker).Scanning electron microscopy (SEM) was conducted for the confirmation of LiP attachment on chitosan beads. The highest textile dye decolorization (95.45%) potential was observed with chitosan-immobilized enzyme at 30°C without hemolytic toxicity. The chitosan beads-LiP retained approximately more than 70% activity after three repeated runs that gradually decreased to 35 % after 7th cycle of reusability. The immobilized LiP was found to show superior dye removal properties as compared to free LiP. Higher thermo stability, lower Kmand high Vmax features of chitosan beads immobilizedLiP suggested its suitibility for variousbiotechnological and industrial applictaions.
Keywords: Schizophyllum commune IBL-06; lignin peroxidase; chitosan beads immobilization; characterization; dye decolorization